(untitled) (Quinto Sol, 2013)
Our objective is to analyze the problems raised by the organization of the ecclesiastical and missionary space, carried out by the Salesians, with the State and the national Church in the organization of the administrative space of Patagonia. The search on the part of the Salesian Congregation for an independent administrative figure –such as the Apostolic Vicariate– from the State and the Vatican, fueled the conflictive relationship with both powers and put in danger the permanence of the Salesian missions in that region.